Analisis Keamanan Sistem Informasi Terhadap Data Pribadi Pada Sosial Media Facebook - rizqy, m rizqy pratama (TEKNOFILE : Jurnal Sistem Informasi, 2025)
The protection of personal data on social media platforms like Facebook has become a crucial issue in the digital age, given the various threats that may arise. This study aims to assess the aspects of personal data security on Facebook using a qualitative descriptive approach. Methods employed include literature review, case study analysis (specifically the Cambridge Analytica case), and semi-structured interviews with Facebook users. The findings reveal that, although Facebook has implemented security measures such as encryption and two-factor authentication, there are shortcomings in its privacy policies and security system implementation. Incidents like Cambridge Analytica highlight weaknesses in personal data protection that need addressing. Interviews with users indicate their lack of understanding regarding privacy settings and data protection. The study recommends enhancing privacy policy transparency, educating users about privacy settings, and applying and evaluating better security technologies to strengthen personal data protection on Facebook.